PLATFORM POWER AND EXPERIENCES FROM THE MARGIN: ADOLESCENTS’ ONLINE VULNERABILITY AND MENTAL HEALTH - Graham, Richard; Stänicke, Line Indrevoll; Jensen, Tine; Livingstone, Sonia; Jessen, Reidar Schei; Staksrud, Elisabeth; Stoilova, Mariya (AoIR Selected Papers of Internet Research, 2023)
Internet and social media use can be both beneficial and harmful for vulnerable youth, offering support and increased self-knowledge, but also exposure to adverse content. Research on the critical question of what makes a difference between the digital pathways to wellbeing or harm is minimal. However, there is some indication that how adolescents engage with the internet and its particular digital affordances makes a difference to their wellbeing outcomes. In this paper, we offer insights into the role of different dimensions of digital engagement in aiding or worsening internet-related mental health difficulties. We report on findings from cross-national comparative qualitative research with 62 adolescents aged 12 to 22 years old from Norway and the UK who experience internet-related mental health difficulties.Findings show that young people actively engage with the digital world both by utilising its affordances but also shaping its parameters, sometimes going against the grain of what was envisioned by design. The adolescents we spoke to were generally skilled internet users, but sophisticated skills do not necessarily make for better mental health and wellbeing outcomes. Independent of digital skill, affordances may result in even riskier online engagement shaped by the operation of algorithms. At times this can breach young people’s abilities to counteract and cope with detrimental consequences. In many cases, we find that the algorithms are “out of sync” with adolescents’ state of mind and ability to cope, exacerbating their mental health difficulties. We conclude with reflections on the implications for platform design and therapeutic support.